2015
DOI: 10.2174/1874325001509010536
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Rupture of the Distal Triceps Tendon (A Series of 7 Cases)

Abstract: Even non-traumatic ruptures of the triceps tendon are rare, surgical therapy should be recommended in all cases, because of poor results after non-operative treatment. A golden standard for the surgical procedure is not established. A small series of traumatic distal tendon ruptures was treated surgical in our hospital and was followed up after 12 months concerning their function. Very good and good results could be found with a strong reintegration of the tendon by using transosseus sutures with non resorbabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…The two described mechanisms for acute tears of the triceps are direct contact trauma, such as a fall or hitting fixed resistance with the posterior elbow[ 5 , 14 , 19 , 21 , 25 ]. Weightlifting[ 1 , 5 , 17 , 19 , 23 - 25 , 27 , 30 ] was the most common sport associated with acute tears and was often associated with a history of steroid use[ 1 , 23 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The two described mechanisms for acute tears of the triceps are direct contact trauma, such as a fall or hitting fixed resistance with the posterior elbow[ 5 , 14 , 19 , 21 , 25 ]. Weightlifting[ 1 , 5 , 17 , 19 , 23 - 25 , 27 , 30 ] was the most common sport associated with acute tears and was often associated with a history of steroid use[ 1 , 23 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous surgical techniques have been reported. These include suture anchors in the triceps footprint[ 5 , 6 , 21 , 25 , 32 ], bone tunnels[ 10 , 14 , 20 , 22 , 31 , 33 ] or a combination of both tunnels and anchors[ 15 , 19 , 33 ]. Suture anchors repairs have also been performed arthroscopically[ 5 , 6 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the vast majority of patients had full strength and range of motion following surgical repair. 17,18,24,41 Other patients were able to return to heavy weight lifting. After repairing TTR, Bach et al 3 reported their patient was able to bench 375 lbs and power clean 407 lbs, whereas Naito et al 23 reported that their patient was able to bench 215 kg at 2 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%